Microentrepreneurs as Socially Responsible Leaders - Simunaniemi Anne-Mari; Valkjärvi Mira; Franzén Riikka; Liikala Sari; Tähtinen Jaana; Suomi Kati; Jeminen Jaana (Sage, 2025)
Corporate social responsibility (CSR) refers to the voluntary integration of social and environmental concerns into companies’ operations. This qualitative case study investigates microentrepreneurs’ values and business activities related to CSR, particularly the elements of social responsibility (SR) via the responsible leadership (RL) approach. We investigate how entrepreneurs perceive the concept of SR, how SR is related to values and through which leadership activities they plan to implement SR. The case is a CSR training programme with 30 Finnish microentrepreneurs as attendants. The results show that entrepreneurs perceive SR on two levels: philosophical and practice-oriented levels. At the philosophical level, RL is being truthful to one’s own values and taking a long-term, holistic view, and the practical SR includes customer focus, staff equality, or community and network activity. Being true to one’s personal values and having a holistic long-term view of SR are the ground-building elements guiding leadership decisions in microenterprises. The practical level of RL is not limited to the microenterprise but, rather, extends to, for example, customers and business partners. The theoretical contribution to the RL literature is that the groundwork for SR in microenterprises is based on strategically sustainable businesses that are in line with entrepreneurs’ values but also simultaneously pursue a greater, more long-term purpose than a short-term profit-seeking. This study adds to the RL literature, indicating that, regardless of their owner-centricity and the focus on practically relevant leadership activities in the here and now, microenterprises pursue larger impacts on the community by adopting a holistic, future-oriented view. Although microenterprises are owner-centric and individual motivations play a significant role in RL, this study shows that, in socially and economically sustainable microenterprises, entrepreneurs’ personal values are integrated with those of the customers.